DIALOGUE IN DISTANCE EDUCATION - T. A. Boronenko; A. V. Kaisina; V. S. Fedotova (Moscow Polytechnic University, 2017)
The purpose of the study is to identify possible forms of organization of dialogical interaction of educational process participants in distance education. Research methods included an analysis of information about capabilities and services of distance learning systems in the organization of dialogue of a teacher and students. The main results are presented in the positioning dialogue as an effective form ofpedagogical interaction, which contributes to the formation ofthe subjective position of a teacher and student, their personal development. The authors show the relevance of the educational dialogue between teacher and students in implicit and explicit form with the use of the powerful potential of modern ICT. The paper adduces examples of electronic discussion within an electronic educational resource. The authors highlight the importance ofexpanding the dialogue interaction in the online space through the use offunctionality of learning management systems, we-binars, blogs, video conferencing, Skype technologies, collaboration with an interactive whiteboard, massive open online courses. All these tools can be effectively used in students' learning process. The paper discusses the perspective areas of research on improving the dialogue interaction in distance education.